Nasopharyngeal Metastasis from Lung Adenocarcinoma: A Case Report and Literature Review - Chiara Conti; Sabrina Nucera; Giuseppe Di Grazia; Federica Martorana; Fabio Motta; Paolo Vigneri; Alfio M. Di Grazia (Case Reports in Oncology)
Introduction: Managing uncommon metastatic sites from different solid tumors is challenging since no available guidelines define the best therapeutic approaches for these rare clinical events. Thus, malignancies giving rise to distant metastases involving infrequent anatomical regions are often associated with a poor prognosis. Case Presentation: We present the case of a 75-year-old man who developed uncontrolled epistaxis following the detection of a metachronous nasopharyngeal metastasis from a previous lung adenocarcinoma. The lesion was identified with a computed tomography scan and its origin from the earlier non-small cell lung cancer was confirmed by a biopsy. The patient was successfully treated with radiation therapy and is currently continuing his oncological follow-up. To the best of our knowledge, this is the fifth reported case of a lung malignancy spreading to the nasopharyngeal region. Conclusion: Meticulous patient monitoring and accurate radiological diagnosis followed by histological confirmation are of paramount importance for the management of uncommon metastatic sites. Likewise, a multidisciplinary approach is essential to devise the appropriate treatment strategy for each patient with locoregional interventions, such as radiation therapy, often playing a pivotal role for the management of symptomatic lesions in unusual anatomical sites.